Cost-Effectiveness of Elbasvir/Grazoprevir for the Treatment of Chronic Hepatitis C: A Systematic Review - Liu, Jinyu; Guo, Min; Ke, Lei; You, Ruxu (Frontiers in Public Health, 2022)
Objective: This study aims to systematically review recent economic evaluations of elbasvir/grazoprevir (EBR/GZR) for chronic hepatitis C (CHC), to critically appraise the reporting quality and to summarize the results. Methods: A literature search was undertaken using Medline, Embase, the Cochrane Library, EconLit, China National Knowledge Infrastructure, Wanfang Data and Chongqing VIP to identify original articles containing economic evaluations of EBR/GZR for CHC published between 1 January 2000 and 31 December 2020. The Consolidated Health Economic Evaluation Reporting Standards statement was used to assess the quality of reporting of the articles. Results: Of 93 articles identified, 13 studies fulfilled the inclusion criteria. These studies were conducted in 4 countries, and 8 active interventions were assessed. The target population was patients infected with CHC genotype 1 infection in all studies. Eight out of 13 studies that compared EBR/GZR versus other direct antiviral agents suggested that EBR/GZR was generally more cost-effective or dominant than daclatasvir/asunaprevir (DCV/ASV), sofosbuvir/velpatasvir (SOF/VEL), ledipasvir/sofosbuvir (LDV/SOF), ombitasvir/paritaprevir/ritonavir+dasabuvir (3D) but not more cost-effective than glecaprevir/pibrentasvir (GLE/PIB). Two studies from China and one study from the USA that compared EBR/GZR versus pegylated interferon and ribavirin (PegIFN/RBV) consistently indicated that EBR/GZR was generally more cost-effective than PegIFN/RBV. One study from Italy compared EBR/GZR with SOF+PegIFN/RBV and suggested that EBR/GZR had a lower cost and higher effectiveness. One study from France and one study from the USA confirmed that compared with nontherapy for patients with chronic kidney disease, EBR/GZR was cost-effective at commonly accepted current standards. All included studies were of good quality of reporting, with an average score of 21.9 (range 19-23). Conclusion: EBR/GZR for CHC genotype 1 might be cost-effective or dominant compared with PegIFN/RBV and other direct antiviral agents (SOF/VEL, 3D, DCV/ASV, LDF/SOF) or nontherapy. However, under certain assumptions, EBR/GZR was not a cost-effective alternative for CHC patients versus GLE/PIB.